ANALYSIS OF SPEECH PROBLEMS BASED ON PEDAGOGICAL-PSYCHOLOGICAL CLASSIFICATION (Educator Insights: Journal of Teaching Theory and Practice, 2026)
The article presents a speech defect and its pedagogical and psychological analysis. The types of speech defects - articulatory, phonetic-phonemic, lexical-grammatical, oral speech retardation and combined disorders - are described in detail. The impact of speech defects on the cognitive, social and emotional development of children, the possibilities of supporting them through corrective and compensatory approaches are also highlighted. The article provides teachers with a scientific basis for the formation of a speech therapy approach and the development of individual programs.